Modernization of Institutional and Economic Management Tools for Environmental Safety of Enterprises - Arthur Amber (Istanbul Management Journal)
This study investigates the institutional and economic mechanisms employed for managing the environmental safety of enterprises in Ukraine and the European Union. Choosing Ukraine as the central focus of this study is deliberate and based on multiple considerations. Ukrainian businesses encounter distinct environmental obstacles due to the country’s unique institutional and economic frameworks. Article enhancements to these mechanisms within the Ukrainian context, leveraging the EU’s experience. The goal is to promote the development of more efficient systems for environmental safety management at enterprises, with an orientation towards sustainable development.The research’s methodological framework is meticulously constructed to be both exhaustive and multidimensional, facilitating a thorough and rigorous investigation of the research subject. This study also integrates synthesis, deduction, logical reasoning, and generalisation to augment the depth and scope of the research outcomes.This study measures to enhance the effectiveness of environmental management systems. These measures include the formulation of an Environmental Safety Code and the Progressive Environmental Management System (PEMS), as well as the creation of an independent Environmental Impact Assessment Authority (EIAA). This study also investigates the potential application of AI in automating the analysis and evaluation of environmental impact scenarios. It proposes the establishment of an Intelligent Environmental Monitoring System (IEMS). Furthermore, the research discusses different types of taxes that could alleviate the adverse environmental effects of businesses. It recommends channelling funds from green bonds into the banking system for green loans or setting up a specialised green investment bank. These measures could incentivize businesses to adopt eco-friendly technologies. This study offers valuable insights for enhancing environmental safety management in businesses and provides practical suggestions for policymakers and business leaders.